PERANAN SUKARMIS DALAM PEMBANGUNAN INFRASTRUKTUR DI KABUPATEN KUANTAN SINGINGI TAHUN 2006-2016 - Silja, Chintia Desma; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Sukarmis is one of the public sector figures in Kuantan Singingi Regency in 2006-2016. Sukarmis was born in Sentajo Raya, June 16, 1956 by parents named Syafiu and Mani Uang. Sukarmis is the fifth of five children. This study aims to (1) determine the background of Sukarmis' life, (2) determine the infrastructure development built by the government of Sukarmis in the field of health, education and transportation infrastructure development and (3) determine Sukarmis's strategy for infrastructure development in Kuantan Singingi. This study uses a mixed research approach between quantitative and qualitative. A quantitative approach was taken to quantitatively determine the volume of infrastructure built during Sukarmis' leadership in Kuantan Singingi Regency. A qualitative approach was taken to determine the background to Sukarmis 'life and then Sukarmis' strategy in building infrastructure in Kuantan Singingi Regency. As a result of this research, Sukarmis served as the first definitive regent in Kuantan Singingi Regency in 2006-2016 and played many roles in the infrastructure development efforts in Kuantan Singingi Regency. The infrastructure development he built has brought many changes and benefits to the people of Kuantan Singingi Regency that are being felt today. He has also made the Kuantan Singingi Regency an example of successful regional autonomy. Sukarmis has built infrastructure in Kuantan Singingi that includes health infrastructure, education infrastructure and transportation that can be felt by the community to remote areas.Key Words: Sukarmis, Infrastructure Development, Strategy, Role